Non-uniform optimal subband beamforming: An evaluation on real acoustic measurements - Nordholm, Sven; Low, S.; Claesson, I.; Yiu, K. (2008)
This paper presents an evaluation of a subband beamforming scheme for speech enhancement and acoustic echo suppression applications, such as hands-free telephony, internet telephony and video conferencing. The aim of the paper is to study the impact of the different types of subband filter banks on the speech enhancement performance. Results show that the octave band filter banks provide an effective means to give an overall efficient processing by using a fewer free filter parameters while providing a similar performance in terms of Signal to Noise Interference Ratio (SNIR) as compared to the uniform case. Whilst the critical band filter bank uses the most subbands, it provides the best performance both objectively and subjectively. This study provides insight to the design of filter bank for future hardware implementations. © 2008 IEEE.